Pengaruh Model Aplikasi Control Diabetes Mellitus Type 2 (CDMT2) Terhadap Kualitas Hidup Pada Pasien Diabetes Mellitus Tipe 2 - Ida Faridah; Ade Purnama; Yati Afiyanti (Poltekkes Kemenkes Surakarta, 2020)
Background: Diabetes mellitus type 2 is incurable but can be controlled by control blood sugar and improves the quality of life of diabetics. The prevalence of diabetes mellitus based on the diagnosis of doctors and the age of ≥15 years in Banten Province increased in 2013 by 1.3% while in 2018 by 2.2% (Riskesdas, 2018). The purpose of this study was to find out the effects of the CDMT2 application model on the quality of life of patients with type 2 diabetes mellitus. Methods: The method in this study is one group of pretest posttest. Sampling techniques in this study used total sampling with a total of 384 respondents with type 2 diabetes mellitus in Banten. The instruments used were the DQOL questionnaire and the cdmt2 application model. Results: Results from quantity analysis using Simple Paired T-Test showed the influence of cdmt2 application model on the quality of life of DM sufferers (value P = 0.000) P <0.05. Cdmt2 application has a real effect on the quality of life of dm type 2 sufferers. Conclusion: The Cdmt2 application model has a noticeable effect on the quality of life of people with type 2 diabetes mellitus health promotion related to type 2 diabetes mellitus.